Language Shift or Maintenance: A Case of Igede Indigenes from Benue State Domicile in Ido Osun in Osun State. Nigeria - Oyeyipo , Damilola Wemimo; Adebileje, Adebola (Corpus Intellectual, 2025)
This paper examines language shift and maintenance among the Igede indigenes from Benue State domiciled in the Ido-Osun community of Osun State, to determine if they are still proficient in the Igede language, language use in different domains, and language attitudes. The data sources for the study were responses from the questionnaires distributed and interviews conducted, alongside personal observations. Utilising Noam Chomsky’s theory of Universal Grammar and Joshua Fishman’s domain as theoretical frameworks, the data were analysed quantitatively and qualitatively. The results reveal that they are proficient in their use of the Igede language despite not living in their community of origin, they use both Yoruba and Igede in the different domains available to them and lastly, they have a good attitude towards their indigenous language. The study shows the attitudes of Igede people to the maintaining of their indigenous language in a host community.